Efficacy and safety of cytoreductive surgery combined with hyperthermic intraperitoneal chemotherapy for epithelial ovarian cancer: a systematic review and updated meta-analysis - Ahmad Azhar Marzuqi; Vincent Enrico Anderson; Latifa Gustina Adilazuardini; Imke Maria Del Rosario Puling; Nyoman Deva Pramana Giri; Alfred Julius Petrarizky (Journal of the Egyptian National Cancer Institute)
Abstract Background The high incidence of primary and recurrent ovarian cancer after surgery imposes a significant economic burden. Cytoreductive Surgery combined with Hyperthermic Intraperitoneal Chemotherapy (CRS + HIPEC) shows promise as a treatment for epithelial ovarian cancer (EOC). This study aims to evaluate CRS + HIPEC’s potential to improve survival outcomes, such as overall survival (OS) and progression-free survival (PFS) while reducing adverse events and enhancing cost-effectiveness. Method A literature review was conducted using the PRISMA framework on databases including Scopus, ProQuest, and PubMed, with quality assessment through the Newcastle–Ottawa Scale (NOS) and Risk of Bias (RoB) 2.0. Quantitative analysis employed RevMan 5.4.1 with a pooled randomized effect model using log [hazard ratio]. Result From 15 studies involving 1982 participants, OS analysis showed significantly higher survival in the CRS + HIPEC group (HR = 0.67, p < 0.0004). Although PFS was higher in this group, the result was not statistically significant (HR = 0.86, p = 0.46). Adverse events were more likely in the intervention group compared to control group (OR = 1.81, p < 0.0001). Cost analysis revealed that the Incremental Cost-effectiveness Ratio per Quality-Adjusted Life Year (ICER/QALY) remains below Indonesia’s GDP threshold. Conclusion CRS + HIPEC shows potential benefits in EOC management, particularly in OS and PFS improvement, alongside manageable adverse events and favorable cost-effectiveness. However, study design heterogeneity, differences in HIPEC protocols, and variations in patient populations limit the generalization of outcomes. The difference in response to HIPEC between primary and recurrent EOCs still needs further explanation.